Stress, mental health and sociocultural adjustment in third culture kids: exploring the mediating roles of resilience and family functioning - Jones, Emma E.; Reed, Marnie; Meyer, Andrea H.; Gaab, Jens; Ooi, Yoon P. (Frontiers in Psychology, 2023)
This cross-sectional study explores the contributions of personal and contextual factors in the adjustment process of a sample of internationally mobile children and adolescents having relocated to Switzerland. Based on evolutionary developmental theories and recommendations by Research Domain Criteria and The Hierarchical Taxonomy of Psychopathology theoretical frameworks, we hypothesized and tested a heuristic model of TCK adjustment, aiming to identify prevention and treatment targets tailored for our sampled population. We assessed the relationships in the hypothesized models, particularly how perceived and acculturative stress influence TCK adjustment and whether the relationship between the predictors of TCK stress and the outcomes of TCK adjustment are mediated by resilience and family functioning. A total of 143 participants aged 7–17, having relocated internationally with their working parent(s), recruited in local and international schools in Switzerland, were included in this study. Data were collected using an online survey after we collected consent. We assessed factors of adjustment using validated questionnaires: perceived stress and acculturative stress and the potential mediating roles of family functioning and resilience. We measured the outcome of adjustment through mental health difficulties and sociocultural adjustment. We used path analysis to test the model. Results highlight the contributions of perceived stress and acculturative stress to TCK mental health and sociocultural adjustment. We also we found a mediation effect for resilience in the relationship between perceived stress and mental health. Family functioning was not a significant mediator in any relationship that we assessed. We discuss implications for future research, promoting TCK adjustment and preventative psychotherapeutic interventions